SCREENING OF RHIZOBACTERIA FOR PLANT GROWTH PROMOTING TRAITS AND ANTIFUNGAL ACTIVITY AGAINST CHARCOAL ROT PATHOGEN MACROPHOMINA PHASEOLINA - T.KAVITHA; R. NELSON; S.JOSEPHIN JESI (International Journal of Pharma and Bio Sciences, 2013)
Plant growth promoting rhizobacteria stimulate plant growth and suppress the colonization of phytopathogens by involving direct and indirect mechanisms. In our investigation ten predominant rhizobacterial isolates belonging to six genera were isolated and characterized for their multiple growth promoting attitudes and antagonistic activity. The results revealed that 70% of the isolates produced phytohormone IAA, 80% of isolates produced ammonia and HCN. Among the ten isolates, four (40%) exhibited phosphate solubilizing and siderophore producing ability. The cell wall degrading enzymes such as cellulase, protease, chitinase activities of isolates were also recorded. They were in the range of 50%, 10% and 60 %, respectively. The antifungal activity of the isolates were tested against Macrophomina phaseolina, among the ten bacterial isolates four (40%) effectively inhibited mycelial growth of plant pathogen. The bacterial strain which showed better results for all the test was identified as Bacillus amyloliquefacience by 16SrRNA sequencing.